Thomas Hobbes - Bunce, R. E. R. (Robin E. R.) (Major conservative and libertarian thinkers, 2009)
In this volume, Dr Bounce (University of Cambridge) introduces Hobbes' ambitious philosophical project to discover the principles that govern the social world. Although we may dispute Hobbes' immodest assessment that he successfully attained this goal, Bunce nevertheless captures the extraordinary enduring value of Hobbes' work for the contemporary reader. Thomas Hobbes's name and the title of his most famous work, Leviathan, have come to be synonymous with the idea that the natural state of humankind is 'nasty, brutish, and short' and only the intervention of a munificent overlord may spare m.